COMPORTAMENTO DE PORTA-ENXERTOS DE VIDEIRA EM SOLO INFESTADO PELA PÉROLA-DA-TERRA - Lourenção, André Luiz; Terra, Maurilo Monteiro; Pires, Erasmo José Paioli; Pommer, Celso Valdevino; Ambrosano, Gláucia Maria Bovi (REVISTA DE AGRICULTURA, 2015)
COMPORTAMENTO DE PORTA-ENXERTOS DE VIDEIRA EM SOLO INFESTADO PELA PÉROLA-DA-TERRA